Non-invasive imaging to monitor lupus nephritis and neuropsychiatric systemic lupus erythematosus [v1; ref status: indexed, http://f1000r.es/5gh] - Joshua Thurman; Natalie Serkova (F1000Research, 2015)
Systemic lupus erythematosus (SLE) is an autoimmune disease that can affect multiple different organs, including the kidneys and central nervous system (CNS). Conventional radiological examinations in SLE patients include volumetric/ anatomical computed tomography (CT), magnetic resonance imaging (MRI) and ultrasound (US). The utility of these modalities is limited, however, due to the complexity of the disease. Furthermore, CT and MRI contrast agents are contraindicated in patients with renal impairment. Various radiologic methods are currently being developed to improve disease characterization in patients with SLE beyond simple anatomical endpoints. Physiological non-contrast MRI protocols have been developed to assess tissue oxygenation, glomerular filtration, renal perfusion, interstitial diffusion, and inflammation-driven fibrosis in lupus nephritis (LN) patients. For neurological symptoms, vessel size imaging (VSI, an MRI approach utilizing T2-relaxing iron oxide nanoparticles) has shown promise as a diagnostic tool. Molecular imaging probes (mostly for MRI and nuclear medicine imaging) have also been developed for diagnosing SLE with high sensitivity, and for monitoring disease activity. This paper reviews the challenges in evaluating disease activity in patients with LN and neuropsychiatric systemic lupus erythematosus (NPSLE). We describe novel MRI and positron-emission tomography (PET) molecular imaging protocols using targeted iron oxide nanoparticles and radioactive ligands, respectively, for detection of SLE-associated inflammation.